Learning from peers: Evidence from disclosure of consumer complaints - Dou, Yiwei; Hung, Mingyi; She, Guoman; Wang, Lynn Linghuan (Journal of Accounting and Economics, 2024)
In 2013, the U.S. Consumer Financial Protection Bureau released a database of consumer complaints filed against banks under its supervision (“CFPB banks”). We find that after the disclosure, rival banks exhibit a greater increase in mortgage approval rates in markets with more intensive mortgage complaints about CFPB banks. The effect is weaker when rivals have more expertise in the local market, are less concerned about credit risk due to mortgage sales, and locate in areas with more alternative information about the CFPB banks. The effect is concentrated in severe complaints and complaints related to loan underwriting practices. In addition to approving more loans, rivals also open more branches and are more likely to post a job opening in these markets. The findings suggest that these banks learn from the nonfinancial disclosures about operational deficiencies of peers (i.e., CFPB banks) in local markets, which alleviates their adverse selection concern about expanding.